On the micro mechanics of yielding and hardening of crushable granular soils - de Bono, John P.; McDowell, Glenn R. (Elsevier, 2018)
Stress path tests are used to investigate the yield surface of a crushable numerical soil. Triaxial samples with isotropic and anisotropic stress histories are examined to determine the nature of the yield surface and to establish what governs yield. Two separate yield surfaces are exposed: a shear yield surface at low p’ and high η which is governed by minor breakage of fine particles, and a compressive yield surface at high p’ and low η, governed by bulk breakage across all particle sizes. The shear yield surface is dependent on stress history, whilst the compressive yield surface is isotropic.